Chromospheric polarimetry through multiline observations of the 850 nm spectral region III: Chromospheric jets driven by twisted magnetic fields. Issue 3 (20th April 2019) - Quintero Noda, C; Iijima, H; Katsukawa, Y; Shimizu, T; Carlsson, M; de la Cruz Rodríguez, J; Ruiz Cobo, B; Orozco Suárez, D; Oba, T; Anan, T; Kubo, M; Kawabata, Y; et al.
ABSTRACT: We investigate the diagnostic potential of the spectral lines at 850 nm for understanding the magnetism of the lower atmosphere. For that purpose, we use a newly developed 3D simulation of a chromospheric jet to check the sensitivity of the spectral lines to this phenomenon as well as our ability to infer the atmospheric information through spectropolarimetric inversions of noisy synthetic data. We start comparing the benefits of inverting the entire spectrum at 850 nm versus only the Ca ii 8542 Å spectral line. We found a better match of the input atmosphere for the former case, mainly at lower heights. However, the results at higher layers were not accurate. After several tests, we determined that we need to weight more the chromospheric lines than the photospheric ones in the computation of the goodness of the fit. The new inversion configuration allows us to obtain better fits and consequently more accurate physical parameters. Therefore, to extract the most from multiline inversions, a proper set of weights needs to be estimated. Besides that, we conclude again that the lines at 850 nm, or a similar arrangement with Ca ii 8542 Å plus Zeeman-sensitive photospheric lines, pose the best-observing configuration for examining the thermal and magnetic properties of the lower solar atmosphere.